2022
DOI: 10.1016/j.breast.2022.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Safety of pre- or postoperative accelerated radiotherapy in 5 fractions: A randomized pilot trial

Abstract: Objective Neo-adjuvant radiotherapy (NART) for breast cancer has shown promising survival results in retrospective trials. However, there are some obstacles such as a chemotherapy delay, an increased overall treatment time (OTT) and the risk of increasing surgical morbidity. Accelerated radiotherapy (RT) in 5 fractions allows to deliver NART in a very short time span and minimizes the delay of surgery and chemotherapy. This trial investigates this NART schedule for safety, feasibility and OTT. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Recent studies have found that adjusting the frequency of neoadjuvant radiation could provide a solution. A randomized pilot trial reported that accelerated neoadjuvant radiation in 5 fractions with a simultaneously integrated boost is feasible and results in a shorter OTT without excess acute toxicity [ 30 ]. Other studies have also explored the role of radiation as a supplement to systemic therapy in this population, but there is still no consensus [ 17 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have found that adjusting the frequency of neoadjuvant radiation could provide a solution. A randomized pilot trial reported that accelerated neoadjuvant radiation in 5 fractions with a simultaneously integrated boost is feasible and results in a shorter OTT without excess acute toxicity [ 30 ]. Other studies have also explored the role of radiation as a supplement to systemic therapy in this population, but there is still no consensus [ 17 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have found that adjusting the frequency of NAR could provide a solution. A randomized pilot trial reported that accelerated NAR in 5 fractions with a simultaneously integrated boost is feasible and results in a shorter OTT without excess acute toxicity [23] . Other studies have also explored the role of radiation as a supplement to systemic therapy in this population, but there is still no consensus [10][24] .…”
Section: Discussionmentioning
confidence: 99%